Monitoring of metals migration and identification of corrosion sources in canned tomatoes and sardines. Issue 16 (16th December 2022) - Safta, Mehdi; Limam, Intissar; Jebali, Raouf; Marzouki, Moomen; Driss, Mohamed R.; Kalfat, Rafik
ABSTRACT: The evaluation of the migration of metallic elements in the metal containers is usually performed through the direct analysis of the cans' content. However, this may be biased by exogenous factors causing contamination of food prior to the canning process. In this context, the separation between exogenous factors and endogenous ones due to the effective migration of metal elements from the containers is often not taken into account. In the present study, we focus on endogenous sources linked to manufacturing defects in metal cans or to the heat treatment operation applied during the canning process. An assessment of the harmless of metal cans was performed for tomato and sardine cans marketed in Tunisia. Cans filled with simulants or food were heat-treated according to industry procedures and stored for an extended period of time. The survey was conducted up to 18 months for cans filled with simulants and until ca. 36 months for those filled with food. Concentrations of potentially migrating metals (Fe, Zn, Cd, Al, Cu, Pb, and Sn) were evaluated using ICP-OES. The inner surface of the cans was examined by SEM/EDX. The obtained results showed high migration levels of Fe and Zn in cans filled with acidic food simulant or tomato paste or sardines in tomato sauce, resulting from corrosion of the inner sides of the cans and the uncoated junction seals. Cadmium was only detected in cans filled with food and is of exogenous origin. Low migration levels of Al, Cu, Pb, and Sn were recorded.